JENIS DATA PENELITIAN KUANTITATIF (Korelasional, Komparatif, Dan Eksperimen) - Aida, Aida; Hermina, Dina; Norlaila, Norlaila (Al-Manba, 2025)
This study aims to explore the types of data used in quantitative research methods, including correlational, comparative, and experimental approaches, as well as their relevance in scientific analysis. The quantitative approach, which is based on numerical data, enables hypothesis testing and result generalization through statistical applications. This paper discusses the primary characteristics of nominal, ordinal, interval, and ratio data, along with their application in each research method. Correlational research identifies relationships between variables, comparative research examines differences among groups, and experimental research tests causal relationships through the manipulation of independent variables. The findings highlight the importance of selecting appropriate data types and research methods to ensure the validity of results. Quantitative research proves to be an effective tool in supporting decision-making and advancing scientific knowledge across various fields.